THE IMPACT OF PELVIC TUMORS ON THE UROGENITAL SYSTEM - Saloxiddinov Eldor Shuxratjon oʻgʻli (Web of Journals Publishing, 2025)
This review explores the impact of pelvic tumors on urogenital function in both pediatric and adult populations. Due to the complex pelvic anatomy, such tumors can lead to bladder dysfunction, ureteral obstruction, renal impairment, and reproductive issues. Advances in molecular classification and targeted therapies have enhanced understanding and management of these conditions. The article highlights pathophysiological mechanisms, clinical features, diagnostic challenges, and treatment strategies, with special attention to pediatric patients. Emphasis is placed on multidisciplinary care combining surgery, radiotherapy, chemotherapy, and supportive interventions to preserve urogenital function and improve outcomes.
Keywords: Pelvic tumors, urogenital system, bladder dysfunction, pediatric oncology, neurogenic bladder, ureteral obstruction, renal function, molecular classification.